Visualization Of Spatial Distribution Of Village Development Index A Review Of Location Data In West Java Province - Riadi, Bambang; Hermawan , Erwin; Hadiyat, Yayan (SOTVI - Society of Visual Informatics, 2024)
The spatial distribution of the Village Development Index (IDM) is the result of village development analysis for the purposes of mapping and assessing variations in the level of village development results in a region. The aim of the research is to analyze the spatial distribution of IDM, which is a comprehensive indicator that covers social, economic and environmental aspects in assessing village development progress. The methodology used in this research includes spatial analysis using a spatial data integration system with secondary data (statistical data). The combination of the internet of things (IoT) with WebGIS makes it possible to integrate data from various sources, in the form of spatial and non-spatial data into one easily accessible platform. This allows for more in-depth and accurate data analysis; and it is possible to disseminate information quickly and widely because it can be accessed by various stakeholders. That spatial distribution of the IDM can be used as an important tool in planning for a more inclusive and sustainable regional development. With WebGIS, data collected from IoT devices can be processed and analyzed to producing interactive maps and reports that will help in a better decision-making process, the research results can be accessed at https://jabar-e.netlify.app.